2021
DOI: 10.1016/j.jbc.2021.100593
|View full text |Cite
|
Sign up to set email alerts
|

PIM-induced phosphorylation of Notch3 promotes breast cancer tumorigenicity in a CSL-independent fashion

Abstract: Dysregulation of the developmentally important Notch signaling pathway is implicated in several types of cancer, including breast cancer. However, the specific roles and regulation of the four different Notch receptors have remained elusive. We have previously reported that the oncogenic PIM kinases phosphorylate Notch1 and Notch3. Phosphorylation of Notch1 within the second nuclear localization sequence of its intracellular domain (ICD) enhances its transcriptional activity and tumorigenicity. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…The structure shows that consistent with our current and previous binding studies ( 22 ) L3MBTL3 binds entirely to the BTD of RBPJ (Figure 3A ), threading through a narrow groove and down the front face of the BTD (Figure 3B – E ). L3MBTL3 residues 56–69 (-KKATATTTWMVPTA-) were built into the electron density; however, the N-terminal lysines ( 56–57 ), which contribute to binding ( see below ), have poorly resolved sidechain density (Figure 3B ). L3MBTL3 residues T63, W64, V66, and P67 bury their sidechains into an exposed hydrophobic pocket on the surface of the BTD, which anchors complex formation, and are flanked N- and C-terminally by an extensive polar network between L3MBTL3 and RBPJ (Figure 3D , E).…”
Section: Resultsmentioning
confidence: 99%
“…The structure shows that consistent with our current and previous binding studies ( 22 ) L3MBTL3 binds entirely to the BTD of RBPJ (Figure 3A ), threading through a narrow groove and down the front face of the BTD (Figure 3B – E ). L3MBTL3 residues 56–69 (-KKATATTTWMVPTA-) were built into the electron density; however, the N-terminal lysines ( 56–57 ), which contribute to binding ( see below ), have poorly resolved sidechain density (Figure 3B ). L3MBTL3 residues T63, W64, V66, and P67 bury their sidechains into an exposed hydrophobic pocket on the surface of the BTD, which anchors complex formation, and are flanked N- and C-terminally by an extensive polar network between L3MBTL3 and RBPJ (Figure 3D , E).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it was shown that Notch3 accelerated the development of prostate cancer-induced bone lesions through MMP-3 ( 35 ). Meanwhile, previous research proved that breast cancer tumorigenesis could be regulated by phosphorylation of Notch3, which might be affected by PTEN transactivation ( 36 38 ). Furthermore, many molecules can also affect tumorigenesis by influencing the Notch3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Notch ICD modifications include phosphorylation, hydroxylation, methylation, sumoylation and acetylation [ 11 ]. Among the kinases phosphorylating Notch are Nemo-like kinases, AKT, CDKs, aPKC, GSK3β and PIM kinases [ 12 , 13 , 14 , 15 , 16 , 17 ]. Phosphorylation by CDK8 in the PEST domain located in the C-terminal part of Notch ICD converts the PEST domain to a phosphodegron [ 18 ], which becomes ubiquitylated by the FBXW7 E3 ubiquitin ligase, inducing rapid proteasome-mediated degradation of Notch ICD [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation by CDK8 in the PEST domain located in the C-terminal part of Notch ICD converts the PEST domain to a phosphodegron [ 18 ], which becomes ubiquitylated by the FBXW7 E3 ubiquitin ligase, inducing rapid proteasome-mediated degradation of Notch ICD [ 19 , 20 , 21 , 22 ]. Phosphorylation by PIM kinases is interesting because it is paralog-specific, i.e., the PIM phosphorylation sites differ between the Notch1 and Notch3 receptors, and PIM-mediated phosphorylation leads to distinct functional consequences for the two receptor paralogs [ 16 , 17 ]. One phosphatase, Eya1, has been identified for Notch ICD, and Eya1-induced removal of a phosphate group from a threonine residue in the transcriptional activation domain of Notch1 ICD increased the stability of Notch1 ICD [ 23 ].…”
Section: Introductionmentioning
confidence: 99%